VTC Spring 2009 - IEEE 69th Vehicular Technology Conference 2009
DOI: 10.1109/vetecs.2009.5073792
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of a UWB Relay System using Multiple Relays with Multiple Antennas in IEEE 802.15.3a Channel

Abstract: In order to coexist with existing legacy wireless systems, the transmit power spectral density (PSD) of ultra-wideband (UWB) impulse radio systems is limited. The coverage range of the UWB systems is then confined within a few meters. One possible way to achieve a greater coverage is a short-range multihop relaying strategy. This paper proposes a two-hop UWB relay system using multiple detect-and-forward relays, each of which is equipped with multiple antennas. Each multiple-antenna relay performs spatial dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Meanwhile, there has been increasing interest in the multi-relay transmissions (also known as cooperative relaying or virtual antenna arrays) [11,29,59,74,83,128,149,162,193,194,257,276]. However, most research studies have focused on the narrowband systems, and further investigations in the UWB case are still ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, there has been increasing interest in the multi-relay transmissions (also known as cooperative relaying or virtual antenna arrays) [11,29,59,74,83,128,149,162,193,194,257,276]. However, most research studies have focused on the narrowband systems, and further investigations in the UWB case are still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…However, most research studies have focused on the narrowband systems, and further investigations in the UWB case are still ongoing. In [149], we presented a two-hop UWB system employing multiple DTF relays. It is found that, to avoid error propagation, the SNR threshold should be properly designed at each relay so that the relay is switched on only when the received SNR exceeds the threshold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tabulated the parameters and mat lab code was given to produce the impulse response of modified S-V channel model. The performance of the relay system in terms of outage probability under IEEE 802.15.3a channel model has been discussed in [6]. Considered a detect-and-forward relay system with multiple antennas equipped in it.…”
Section: Literature Reviewmentioning
confidence: 99%